Video-based calcification assay: A novel method for kinetic analysis of osteogenesis in live cultures - Ivann KC Martinez; Bir Bhanu; Nicole I zur Nieden (MethodsX, 2021)
Traditional methods of quantifying osteoblast calcification in culture require the use of calcium sensitive dyes, such as Arsenazo III or Alizarin Red S, which have been successfully used for decades to assess osteogenesis. Because these dyes elicit a colorimetric change when reacted with a cell lysate and are cytotoxic to live cells, they forfeit the ability to trace calcification longitudinally over time. Here, we demonstrate that image analysis and quantification of calcification can be performed from a series of time-lapse images acquired from videos. This method capitalizes on the unique facet of the mineralized extracellular matrix to appear black when viewed with phase contrast optics. This appearance of calcified areas had been previously documented to be characteristic to the formation of bone nodules in vitro. Due to this distinguishable appearance, extracting the information corresponding to calcification through segmentation allowed us to threshold only the pixels that comprise the mineralized areas in the image. Ultimately, this method can be used to quantify calcification yield, rates and kinetics facilitating the analyses of bone-supportive properties of growth factors and morphogens as well as of adverse effects elicited by toxicants. It may also be used on images that were acquired manually. • The method is less error-prone than absorption-based assays since it takes longitudinal measurements from the same cultures • It is cost effective as it foregoes the use of calcium-sensitive dyes • It is automatable and amenable to high-throughput and thus allows the concurrent quantification of multiple parameters of differentiation